Positioning in the global value chain as a sustainable strategy: A case study in a mature industry - Jose Albors-Garrigos; Blanca De Miguel Molina; Maria De Miguel Molina (Administrative Sciences, 2014)
As a result of the development of new industrialized countries, such as Brazil, China and other Southern Asian economies, as well as a globalized economy, traditional competitive paradigms based on advantages associated with costs and quality efficiencies or even innovation are no longer sufficient. These previous classical paradigms related competitiveness either to costs or technology innovation and the resources of industry incumbents. However, the combination of adequate knowledge and relationship management with marketing efforts brings forth a reconsideration of the present competitive models that go beyond those analyses from the point of view of global value chains. The objective of this investigation will analyze the governance structure of the territorial value chain in the Spanish and Italian ceramic tile industry, through the understanding of the previous and current roles of several industries involved in the value creation system. By way of both a case study and quantitative methodology approach, we will explore the paradigm change where traditional chain actors are losing their grip on their contribution to the territorial value creation system as new actors appear with a more stable status. The article concludes that proper positioning in the global value chain is a key strategy for the sustainability of the involved firms, especially Small and Medium Enterprises (SME).
Keywords: 350; clusters; innovation systems; value chain